Floating-point division and square root using a Taylor-series expansion algorithm - Taek-Jun Kwon; Sondeen, J.; Draper, J. (2007 50th Midwest Symposium on Circuits and Systems, 2007)
Hardware support for floating-point (FP) arithmetic is a mandatory feature of modern microprocessor design. Although division and square root are relatively infrequent operations in traditional general-purpose applications, they are indispensable and becoming increasingly important in many modern applications. Therefore, overall performance can be greatly affected by the algorithms and the implementations used for designing FP-div and FP-sqrt units. In this paper, a fused floating-point multiply/divide/square root unit based on Taylor-series expansion algorithm is proposed. We extended an existing multiply/divide fused unit to incorporate the square root function with little area and latency overhead since Taylor's theorem enables us to compute approximations for many well-known functions with very similar forms. The proposed arithmetic unit exhibits a reasonably good area- performance balance.